Gestión de residuos sólidos domiciliarios y la calidad ambiental en la provincia de Ucayali-Contamana 2023 - Reategui Nuñez de Monteza, Kelita Margoth (2024)
The objective of this thesis report was to determine the relationship between household solid waste management and environmental quality in the province of Ucayali-Contamana 2023, opting for an applied study with a non experimental design, taking 376 inhabitants as a sample. A questionnaire of questions was used to them. The results show that the management of household solid waste is regular with 29%, this is because the municipality sometimes complies with the regulations and has established procedures for the selective collection and proper management of solid waste. It is also responsible for supervising the conditions of the vehicle units used to transport this waste and the punctuality of the collection service. For its part, environmental quality is at a medium level (28%), since occasional maintenance of water sources is carried out. However, in the district's markets you can constantly smell bad odors caused by the accumulation of garbage. Despite this, the municipality sometimes carries out campaigns to keep public spaces clean. Finally, it was determined that there is a strong correlation between the variables, being contrasted by a Spearman's Rho coefficient of 0.854 and a significance (p-value) of 0.000.